Northern Alaska’s portable planetarium before, during, and after the heliophysics big year - Smith, Austin R.; Meurlott, Kalee; Sakhalkar, Soumitra; Storm, Kaz; Taylor, Kelly; Chaudhuri, Ankana; McGilvary, Lynda; Sellers, Victoria; Fischer, Heather (Frontiers in Astronomy and Space Sciences, 2025)
The University of Alaska, Fairbanks has operated a portable planetarium for nearly two decades. This planetarium has visited remote communities, both on and off Alaska’s limited road network, teaching heliophysics and astronomy concepts to students and the public. Over the past 3 years, 33 events have reached thousands of people. At 21 of these, voluntary questionnaires were given to attendees after a planetarium show. These short questionnaires have only four questions, covering science comprehension and enthusiasm, as well as limited demographic information. In this work the results from 902 questionnaires are presented, together with lessons learned from the variety of events and locations the planetarium has visited since 2023. Half of the questionnaire responses are from visitors aged 10–13, highlighting our focus on elementary and middle school students and the sound system has been improved as suggested from comments left on the questionnaire.